HUBUNGAN TINGKAT PENGETAHUAN MAHASISWA TERHADAP RASIONALITAS PENGGUNAAN OBAT ANTIBIOTIK - Andre; Irda Rizky Wiharti; Erin Efrilia (Universitas Pekalongan, 2025)
Antibiotics are among the most commonly used drugs to treat infections. However, their use is often accompanied by misunderstandings and a lack of knowledge regarding proper usage. Pharmacy students, as health science students who study medicines, are expected to have a good understanding in order to provide accurate information about drugs within their community. The purpose of this study is to determine the level of knowledge about antibiotics among pharmacy students at the University of Pekalongan. The method used in this study was a questionnaire distributed using random sampling, involving 108 student respondents. Based on the results, the level of respondents' knowledge was categorized as good in 77.6% of the participants. Keywords: Knowledge, Pharmacy Students, Medication Use, Antibiotic